فن الزخرفة في الجزائر خلال العهد العثماني قسنطينة أنموذجا - طواهرية غزالة; عمامرة نعيمة (My University, 2021)
Abstract : Our searis to study the subjectif of art and de curation in Alegria during the ottoman era (Constantin as modal) ,the importances of stydying art in Constantine dnring the ottoman eralies in knowing its purpose and inportance ,and its indnstries in Constantine witch we learned throngh Our study of its origin history and geographie witch mandait the formes of the foll owing forms what are additions made by the city of Constantine a historical and archeologicalcity in torms of its decorations that are stile to this day ? ----------------------------------------- ملخص: يهدف بحثنا إلى دراسة موضوع الفن والزخرفة في مدينة أليجريا خلال العصر العثماني (قسطنطين نموذجًا)، وأهمية دراسة الفن في قسنطينة خلال العصور العثمانية في معرفة غايته وأهميته، وصناعاته في قسنطينة التي تعلمناها من خلال دراستنا لتاريخه وجغرافيته، والتي تتطلب أشكالًا من الأشكال التالية: ما هي الإضافات التي أضافتها مدينة قسنطينة، المدينة التاريخية والأثرية، إلى زخارفها التي لا تزال قائمة حتى يومنا هذا؟
Keywords: الفن، الزخرفة، قسنطينة، العصر العثماني، الحرفيون، المبدعون